Pemanfaatan Jahe Merah (Zingiber Officinale Var. Rubrum) dalam Mengatasi Mual, Nyeri Otot, dan Inflamasi Pada Penderita Flu (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to explore the effectiveness of consuming red ginger (Zingiber officinale var. rubrum) decoction in relieving flu symptoms, including nausea, muscle pain, and inflammation, as well as examining users' subjective experiences in the context of local wisdom-based health practices. The study was conducted using a true experimental randomized pretest-posttest control group design combined with a qualitative approach. Ten respondents who met the inclusion criteria were recruited and then randomized into a treatment group and a control group. The treatment group consumed red ginger decoction twice a day, while the control group did not receive any intervention. Data were collected through in-depth interviews, observations, and documentation, and then analyzed thematically by comparing symptom scores before and after the intervention. The results showed that the treatment group experienced the most significant reduction in nausea intensity, followed by a reduction in muscle pain and inflammation, while the control group showed only minimal changes. The rapid response to nausea was an interesting finding that confirmed the potential of red ginger as a complementary therapy for flu. This study showed that the use of red ginger is not only effective in reducing symptoms but also easy to apply in a household context, thereby potentially strengthening efforts towards family health independence.